2022
DOI: 10.1097/bpo.0000000000002253
|View full text |Cite
|
Sign up to set email alerts
|

Motorized Plate Lengthening of the Femur in Children: A Preliminary Report

Abstract: Background: Limb lengthening by distraction osteogenesis can be performed with motorized internal devices, but intramedullary implants risk avascular necrosis of the femoral head in young children. A method of internal limb lengthening using a motorized expandable plate has been developed and preliminary results are presented. Methods: Seven skeletally immature patients (ages 2.7 to 9.7 y) with congenital femoral deficiencies underwent femoral lengthening with the use of a magnetic expandable plate. Surgical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The preliminary results showed mean lengthening of 4.1 cm over 50.2 days with weight-bearing at 13 weeks. Complication rates were similar to other methods of femoral lengthening, but the authors noted that careful planning was necessary to mitigate further complications 23 .…”
Section: Limb Deformity and Reconstructionmentioning
confidence: 59%
“…The preliminary results showed mean lengthening of 4.1 cm over 50.2 days with weight-bearing at 13 weeks. Complication rates were similar to other methods of femoral lengthening, but the authors noted that careful planning was necessary to mitigate further complications 23 .…”
Section: Limb Deformity and Reconstructionmentioning
confidence: 59%
“…24 In another cohort of seven patients with CFD and/or FH age 3 to 10 years, lengthening was performed using a magnetic expandable plate. 48 Complications encountered included one hip subluxation, one knee flexion contracture and varus deformity in three patients.…”
Section: Congenital Deficienciesmentioning
confidence: 96%
“…Preliminary clinical results have shown that limb lengthening with motorized internal plates is feasible in very young children. 48 In addition, a preclinical animal study has reported on continuous lengthening by osmotic pumps that might be used for bone distraction. 49 …”
Section: Internal Nail Lengtheningmentioning
confidence: 99%
“…A magnetically driven plate was developed for physis-sparing lengthening in young children. A case series of 7 patients with a mean age of 6.1 years reported successful femoral lengthening, with 3.3 to 4.4 cm achieved, although 5 of 7 patients had complications 61 .…”
Section: Lower-extremity Alignment and Deformitymentioning
confidence: 99%